Macroeconomic Issues Facing ASEAN Countries. (International Monetary Fund, 1997)
This volume, edited by John Hicklin, David Robinson, and Anoop Singh, contains papers prepared for an ASEAN conference held in Jakarta in November 1996. The conference aimed to review the macroeconomic record of the member countries of ASEAN, examine the factors that have contributed to the region's economic success, and identify the policy agenda for sustaining this success into the 21st century.